A potent voltage-gated calcium channel inhibitor engineered from a nanobody targeted to auxiliary Ca(V)β subunits - Morgenstern, Travis J (eLife, 2019)
Inhibiting high-voltage-activated calcium channels (HVACCs; Ca(V)1/Ca(V)2) is therapeutic for myriad cardiovascular and neurological diseases. For particular applications, genetically-encoded HVACC blockers may enable channel inhibition with greater tissue-specificity and versatility than is achievable with small molecules. Here, we engineered a genetically-encoded HVACC inhibitor by first isolating an immunized llama nanobody (nb.F3) that binds auxiliary HVACC Ca(V)β subunits. Nb.F3 by itself is functionally inert, providing a convenient vehicle to target active moieties to Ca(V)β-associated channels. Nb.F3 fused to the catalytic HECT domain of Nedd4L (Ca(V)-aβlator), an E3 ubiquitin ligase, ablated currents from diverse HVACCs reconstituted in HEK293 cells, and from endogenous Ca(V)1/Ca(V)2 channels in mammalian cardiomyocytes, dorsal root ganglion neurons, and pancreatic β cells. In cardiomyocytes, Ca(V)-aβlator redistributed Ca(V)1.2 channels from dyads to Rab-7-positive late endosomes. This work introduces Ca(V)-aβlator as a potent genetically-encoded HVACC inhibitor, and describes a general approach that can be broadly adapted to generate versatile modulators for macro-molecular membrane protein complexes.